KNOWLEDGE AND HEALTH SEEKING BEHAVIOR RELATED TO KALA-AZAR IN RURAL COMMUNITIES OF EAST CHAMPARAN DISTRICT, BIHAR - Kumar, Navin; B, Singh T; P, Meena L (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To find out the sociodemographic characteristics, knowledge and health seeking behavior related to KA in the East Champaran district, Bihar among study subject. Methods: A case-control study was conducted to understand the knowledge and health seeking behavior related to KA in the East Champaran district. A total of 100 KA cases and 100 healthy controls selected from the neighborhoods of cases. Results: The knowledge of the population showed that the male constituted 58% of the total population in which 56% were case and 60% were control. Majority of the respondent 76.5% were aware from the KA. Maximum of the respondent 72.5% believed that biting time of sand flies were in the night. Moreover, 71% respondent cannot know how to protect the KA transmission. Conclusion: These results will be useful for further improvement in the KA control programs for intervention strategies. The knowledge of the study subject about KA, the vectors, the transmission of KA, and control measures was poor which needs some effort of the public health system by the Ministry working in the field of health.